Social Media Health Prevention Strategies for Hospitals to Captivate Young Adults' Interest - Amalia Putri Ocean; Mahendro Prasetyo Kusumo (Universitas Muhammadiyah Yogyakarta, 2024)
Social media has the potential to be used by hospitals to play their role as health-promoting hospitals. By utilizing social media, hospitals can perform health prevention services at a reasonable cost. Nowadays, youths are more likely to suffer non-communicable diseases (NCD) like Diabetic Mellitus due to lifestyle changes that are sedentary. However, most youths consider that health promotion messages that already exist are unappealing. The purpose of this study is to determine the relevant strategy to deliver a health promotion message through social media that can captivate the youth’s interest. This study is a qualitative study with a phenomenology design. Data collection was carried out from three focus group discussions (FGD) that were selected by purposive and selective sampling methods. The data was then analyzed with the inductive theme analysis method. Triangulation and transferability tests were conducted to assess the validity of this study. Health promotion delivery must ensure that the message is attractive and easy to understand To expand the target audience's understanding. Health promotion should be done by considering what the message is, who the target is, what kind of content is, and on what platform. Besides, the content should be relevant, entertaining, credible, and easy to be understood.